Estimation of Essential and Toxic Mineral Elements in Mentha Species - Ali Ebrahimzadeh, Mohamamd; Eslami, Shahram; Mohammad Nabavi, Seyed; Fazel Nabavi, Seyed; Hajizadeh Moghaddam, Akbar; Reza Bekhradnia, Ahmad (Asian Journal of Chemistry, 2010)
The objective of the study is to estimate the essential and toxic mineral elements using atomic absorption spectrophotometer (AAS), in four Mentha species aerial parts including Mentha aquatica, Mentha longifolia, Mentha spicata and Mentha piperita. Among the 8 elements analyzed, iron, manganese and zinc were the most abundant element distributed throughout all of these species. The highest amounts found in M. spicata with 129.76 μg/g of Fe, 8.52 μg/g of Zn and 6.8 μg/g of Mn. It is the best source for useful trace elements.